Leakage-Resilient Cryptosystem with Efficient and Flexible Key Delegation in Scalable Cloud Storage - sarika, M; Sasikiran, J; Sunitha, L; Koteswara Rao, D (International Journal of Computer Sciences and Engineering, 2025)
We present a generic construction of a public key encryption scheme that is resilient to key leakage from any hash proof system. The construction does not rely on additional computational assumptions, and the resulting scheme is as efficient as the underlying hash proof system. Existing constructions of hash proof systems imply that our construction can be based on a variety of theoretic assumptions. We achieve leakage-resilience under the respective static assumptions of the original systems in the standard model, while also preserving the efficiency of the original schemes.